CRMP2-derived peptide ST2-104 (R9-CBD3) protects SH-SY5Y neuroblastoma cells against Aβ25-35-induced neurotoxicity by inhibiting the pCRMP2/NMDAR2B signaling pathway. (25th May 2019) - Ji, Yingshi; Hu, Yang; Ren, Jinghong; Khanna, Rajesh; Yao, Yuan; Chen, Yang; Li, Qi; Sun, Li
Abstract: Collapsin response mediator protein 2 (CRMP2), by regulating voltage-gated calcium channel activity, is a crucial regulator of neuronal excitability. Hyperphosphorylation of CRMP2 has been reported in brains of Alzheimer's disease (AD) patients and other neurodegenerative diseases. CRMP2 acting on N -methyl- d -aspartate receptors (NMDARs) may contribute to AD pathology. A short peptide from CRMP2, designated the Ca 2+ channel-binding domain 3 (CBD3) peptide, has recently emerged as a Ca 2+ channel blocker that exerts neuroprotective effects in traumatic brain injury and cerebral ischemia by disrupting pCRMP2/NMDAR interaction to inhibit calcium influx. ST2-104, a nona-arginine (R9)-conjugated CBD3 peptide derived from CRMP2, exerts a beneficial effect on neuropathic pain; however, the effect of ST2-104 on AD and its mechanism of action have not been studied. In this study we investigated the effects of ST2-104 on SH-SY5Y neuroblastoma cells stimulated by Aβ25-35 . To induce neurotoxicity, SH-SY5Y cells were incubated with Aβ25-35, the shortest toxic fragment of Aβ. CRMP2 expression was manipulated by knockdown or overexpression of CRMP2 before ST2-104 treatment to further explore if the pCRMP2/NMDAR2B signaling pathway is involved in the action of the ST2-104 peptide. The results show that ST2-104 significantly enhanced cell viability, inhibited cell apoptosis, decreased LDH release, suppressed the expression of the pCRMP2 protein, disrupted pCRMP2/NMDAR2B interaction, inhibited Aβ25-35 -induced NMDAR currents, and decreased intracellular Ca 2+ levels. The effects of ST2-104 was abolished by overexpression of CRMP2 and intensified by knockdown of CRMP2 in SH-SY5Y cells. Taken together, our results support ST2-104 as a possible biologic therapeutic in the face of Aβ25-35 -induced injury via the inhibition of the pCRMP2/NMDAR2B signaling pathway. Highlights: ST2-104 inhibited Aβ25-35 -induced NMDAR currents in SH-SY5Y cells. ST2-104 decreased intracellular Ca 2+ levels in SH-SY5Y cells. ST2-104 relieved neuronal injury by suppressing pCRMP2/NMDAR2B pathway.